Clinical Study Of Enteropathogenic Which Causes Diarrhea Among 0-15 Years Age Group In Baghdad (Journal of the College of Basic Education, 2022)
Diarrheal diseases are a leading cause of mortality among children in developing countries. This study is designed to investigate the bacterial, viral and parasitic etiology and related clinical and epidemiological factors in children among 0-15years age group with diarrhea in Baghdad city. A total of 200 sample of the stool obtained from children with diarrhea visiting child ̓s Central Teaching Hospital and Alkadhmiya Hospital for children in the period between April , 2016 to October , 2016 . Stool sample were examined by using standard culture and identification methods for bacteria , and by microscopically using normal saline and iodine staining wet mounts for identification of parasites and by Rapid Diagnostic Kit for detection of rotavirus. From summation of 200 cases in the study group ,144(72%) infected by single etiology and 56(28%) infected by mixed etiology . The highest infection rate recorded in the bacterial group (51.5%) followed by parasitic group (37.5%) and viral group (11%) . According to the age categories , it was observed that maximum bacterial infection rate at age group (< 1 years ) were (46%), while at age group (> 5 years) were (52%) for maximum parasitic infection and viral infection recorded the highest rate in the age group (1-5 years) by 73% . The result of the study showed that the predominant bacteria were Escherichia coli with 20.5% followed by Shigella sp. , Salmonella sp. and Klebsiella sp. with 14.5% , 10% and 6.5% respectively . Entamoeba histolytica recorded highest parasitic infection rate 19.5% followed by Giardia lamblia 12.5% and Blantidium coli 5.5% . The percentage of samples infected with rotavirus was 11% compared with the total number of samples studied .